Щодо визначення ризиків та загроз в умовах фактичної втрати частини території та економічного потенціалу старопромислових регіонів - Снігова, О.Ю. (Економіка промисловості, 2015)
Проаналізовано умови формування ризиків та загроз для України, що походять із втрати частини територій та економічного потенціалу старопромислових регіонів. Встановлено перелік ризиків і загроз для України у цілому та для територій Донецької і Луганської областей, непідконтрольних українській владі. З'ясовано, що найбільший негативний вплив на економіку України має втрата частини економічного потенціалу старопромислових регіонів та ескалація конфлікту на Сході країни. Проанализированы условия формирования рисков и угроз для Украины, обусловленных потерей части территории и экономического потенциала старопромышленных регионов. Определен перечень рисков и угроз для Украины и для территорий Донецкой и Луганской областей, неподконтрольных украинской власти. Установлено, что наибольшее негативное влияние на национальную экономику Украины оказывает потеря части экономического потенциала старопромышленных регионов и эскалация конфликта на Востоке Украины. The article argues that escalation of the conflict at Donbas region has the primordial influence on the situation in Ukrainian economy. The statistical analysis of economic situation in Donetsk and Lugansk regions has been conducted. The financial and economic consequences of control loss over parts of Donetsk and Lugansk regions have been studied. It has been determined that Ukraine is subject to credit risks, despite restructuring and plans of reforms. It has been revealed that the most negative influence on the economy of Ukraine goes from the instability and uncertainty of situation at the East of Ukraine, loss of a prevalent part of industrial and natural potential of old industrial regions, investment attractiveness reduction and loss of confidence for banking sector. It has been argued that natural potential losses roughly deteriorate the energy security of a country based on coal share enlargement in energy balance and shell gas role increase in the fight for gas independence and natural gas price reduction. It has been determined that the loss of a part of industrial and natural potential, based at the territory uncontrolled by Ukraine, has been added by the increased risks for industrial enterprises‟ functioning practically at all territory of those and frontier regions due to diversions and terrorist acts threats. The factors deteriorating investment attractiveness of Donetsk and Lugansk regions have been found out. The possible losses of banking sector have been estimated connected with cancelling of clients‟ service at the territory, uncontrolled by Ukrainian authority. The influence of banking sector crisis on business activity shortening in Ukraine, and, in particular, on the industrial enterprises, forming basic branches of old-industrial regions, has been revealed. Risks and threats for Ukraine caused by the conflict at the East of Ukraine, have been determined. Recommendations as to stabilize macroeconomic processes and ease consequences for Ukraine have been given.